2020
DOI: 10.3390/antiox9030265
|View full text |Cite
|
Sign up to set email alerts
|

Water Ultrasound-Assisted Extraction of Polyphenol Compounds from Brewer’s Spent Grain: Kinetic Study, Extract Characterization, and Concentration

Abstract: Brewer’s spent grain (BSG) was chemically characterized obtaining 52.1% of carbohydrates, 17.8% protein, 5.9% lipids, 13.5% insoluble lignin and 24.3% of water-soluble extractives. This work has been focused on the study of polyphenol extraction of the extractive fraction by water ultrasound-assisted extraction. Selected extraction conditions were 47 °C and 21.7 mL water/gdry-BSG. The effect of solvent polarity on polyphenol extraction was studied by using ethanol aqueous mixtures, from 20% to 100% ethanol. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 21 publications
(35 reference statements)
4
48
0
2
Order By: Relevance
“…Experimental data were in good agreement with both power law and the Weibull model [ 101 ]. Ultrasound-assisted extraction achieved similar productivity, after 30 min of treatment, in comparison to enzyme hydrolysis [ 101 ]. Birsan et al compared conventional maceration, microwave and ultrasound-assisted extraction, using BSG from light and dark beer as well as their mixtures [ 102 ].…”
Section: Extraction Of High-value Compounds From Bsgmentioning
confidence: 67%
See 2 more Smart Citations
“…Experimental data were in good agreement with both power law and the Weibull model [ 101 ]. Ultrasound-assisted extraction achieved similar productivity, after 30 min of treatment, in comparison to enzyme hydrolysis [ 101 ]. Birsan et al compared conventional maceration, microwave and ultrasound-assisted extraction, using BSG from light and dark beer as well as their mixtures [ 102 ].…”
Section: Extraction Of High-value Compounds From Bsgmentioning
confidence: 67%
“…Alonso-Riaño et al characterized extraction, and determined kinetics of the water, ultrasound-assisted extraction of polyphenol compounds from BSG [ 101 ]. Experimental data were in good agreement with both power law and the Weibull model [ 101 ].…”
Section: Extraction Of High-value Compounds From Bsgmentioning
confidence: 99%
See 1 more Smart Citation
“…A great deal of effort has been made to explain the influence of temperature on the extraction. In this sense, studies have shown that temperature increase has a direct effect by increasing the rate of extraction [ 101 , 102 ]. Some results reported in the literature have shown a second-order kinetic in which the rate of extraction decreased with increasing temperature for the extraction of polyphenols from Humulus lupulus [ 103 ].…”
Section: Mechanical Force Methodsmentioning
confidence: 99%
“…Biological activity of these residues makes long term storage difficult. The literature reports ongoing work on various new ways of using BSG, including extraction of polyphenols [10,11], other anti-oxidants [12,13], functional cardioprotective lipids for pharmaceutic use [14], proteins [15], fodder for edible insects [16], material for disposable trays [17], natural rubber modifier [18], as well as feedstock for production of pigments [19] and biochar, for subsequent use as soil amendment [20] or sustainable material for electrodes [21].The potential use of this residue as a fuel has been suggested by several authors so far [7][8][9]22,23]. The relatively high initial moisture content of spent grain makes hydrothermal valorization techniques the most sensible choice [8,9].…”
mentioning
confidence: 99%